2013
DOI: 10.1007/s40265-013-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

HIV Protease Inhibitors in Pregnancy

Abstract: The impact of antiretroviral therapy (ART) on the natural history of HIV-1 infection has resulted in dramatic reductions in disease-associated morbidity and mortality. Additionally, the epidemiology of HIV-1 infection worldwide is changing, as women now represent a substantial proportion of infected adults. As more highly effective and tolerable antiretroviral regimens become available, and as the prevention of mother-to-child transmission becomes an attainable goal in the management of HIV-infected individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 127 publications
1
4
0
1
Order By: Relevance
“…It is known that protease inhibitors can cause lipid metabolic changes, metabolic syndrome, lipodystrophy, changes in the carbohydrate metabolism and increased cardiovascular risk in every HIV infected patient [ 47 49 ]. Some studies had demonstrated that during pregnancy women in use of PI also presented higher rates of dyslipidemia, metabolic syndrome, lipodystrophy, diabetes and pre-eclampsia [ 50 – 52 ], as some of our data also demonstrated.…”
Section: Discussionsupporting
confidence: 84%
“…It is known that protease inhibitors can cause lipid metabolic changes, metabolic syndrome, lipodystrophy, changes in the carbohydrate metabolism and increased cardiovascular risk in every HIV infected patient [ 47 49 ]. Some studies had demonstrated that during pregnancy women in use of PI also presented higher rates of dyslipidemia, metabolic syndrome, lipodystrophy, diabetes and pre-eclampsia [ 50 – 52 ], as some of our data also demonstrated.…”
Section: Discussionsupporting
confidence: 84%
“…Of the 3 different classes of drugs tested—NRTIs, nonnucleoside reverse transcriptase inhibitors (NNRTIs), and PIs—only PIs resulted in reduced progesterone levels (Figure 1 A ). RTV, known for its significant impact on CYP enzymes [ 20 ], had the strongest inhibitory effect on progesterone levels. ATV and LPV also decreased progesterone levels, while darunavir (DRV) was the only PI tested that did not significantly affect progesterone release.…”
Section: Resultsmentioning
confidence: 99%
“…Progesterone is synthesized from maternal cholesterol, and its synthesis, metabolism, and clearance depend on a variety of enzymes, many belonging to the cytochrome (CYP) family. PIs, especially ritonavir (RTV), affect the expression and activity of CYP enzymes [ 20 ], and it has been speculated that this is a mechanism through which PIs could alter sex steroid hormone levels [ 21 , 22 ]. Elevated 17-hydroxyprogesterone and dehydroepiandrosterone-sulfate levels suggestive of adrenal dysfunction have been reported in neonates exposed perinatally and postnatally to RTV-boosted lopinavir [ 23 ].…”
mentioning
confidence: 99%
“…Previous studies on PTB have generally considered PIs as a single group for comparison against no treatment, non-nucleoside reverse transcriptase inhibitor (NNRTI) or nucleoside reverse transcriptase inhibitor (NRTI) based regimens, not distinguishing whether they were used with or without ritonavir (RTV) boosting [20]. However, RTV, used individually or as a boosting agent, has its own unique side-effect profile.…”
Section: Introductionmentioning
confidence: 99%